A crise da pós-modernidade e o militante católico de direitos humanos no período de 1980 a 2000, no cenário recifense - Castro, José Roberto Wanderley de (2007)
The present study it has as objective to perceive the impact of the crisis of the after-modernity on the catholic militants in defense of the Human Rights in Recife, in the historical period of 1980 the 2000. How to perceive the militancy after the exit and Dom Helder? Making the use of the theories of Gramsci to construct the research universe, and thus to perceive the reach of the crisis of after-modernity in the militant ones. The universe of the research was composed for professors of course of Theology of the Catholic University who had militated in the historical period of the present research. Using personal interviews, it was possible to conclude that, as well as all the ones that compose the society and its estamentos, the militant ones had suffered the effect from after-modernity, what it reflected in its performance